Højaltertavlen i Hviding ved Ribe: Tavlens ikonografiske program og dens kirkehistoriske/kirkepolitiske placering lokalt og internationalt - Frederiksen, Hans Jørgen (Hikuin, 1999)
The alterpiece in Hviding by Ribe. The iconographic programme of the alterpiece and it’s churchhistorical/churchpolitical placing locally and internationally By Hans Jørgen Frederiksen The alterpiece was carved c.1520. It’s main theme is The Trinity and Ecclesia Triumphans within a circular rosary. The alterpiece relates to a woodcut from 1514/15 by Erhard Schön from Nürnberg. The subject is a so called indulgence-motive typical for the last decades of the medieval periode. The fact that the alterpiece survived the lutheran reformation is most remarkable. Many works of art from catholic times did in fact survive but only very few with an iconography so “papistic” as this.